Determinants of Earnings Management: Deferred Tax, Tax Planning, Firm Size with Institutional Ownership as Moderator - Eko Sudarmanto; Ahmad Waluya Jati; Junet Kaswoto; Mega Arum; Kristanti Rahman (Penerbit Goodwood, 2026)
Purpose: This study examines the effects of deferred tax expense, tax planning, and firm size on earnings management, with institutional ownership as a moderating variable. Research Methodology: This study employs a quantitative approach using secondary data from companies in the primary consumer goods sector listed on the Indonesia Stock Exchange over the 2019–2023 period. Purposive sampling identified 14 firms. The analysis was conducted using panel data logistic regression. Results: The findings reveal that deferred tax expenses significantly affect earnings management. In contrast, tax planning and firm size did not show significant effects. Additionally, institutional ownership moderates the relationship between deferred tax expenses and earnings management but does not moderate the relationships involving tax planning and firm size. Conclusions: Deferred tax expense is a key determinant of earnings management, whereas tax planning and firm size are not. Institutional ownership plays a selective moderating role and is effective only in the context of deferred tax-related discretion. Limitations: This study is limited by its relatively small sample size (14 firms) and focus on a single sector, which may restrict the generalizability of the findings. Additionally, the model explained a limited proportion of the variance, indicating the presence of other unexamined factors. Contributions: This study contributes to the literature by showing that deferred tax expense is a key earnings management driver and institutional ownership is a selective governance mechanism, and by providing empirical evidence from an emerging market on taxation, firm traits, and earnings management.